A sliding mode controller for a model of flow separation in boundary layers. (9th December 2019) - Sanchez, Tonametl; Polyakov, Andrey; Richard, Jean‐Pierre
Summary: In this paper, we propose a sliding mode controller for a MIMO model of flow separation in boundary layers. The model consists in a bilinear system with constant delays in both the state and the input. The main motivation to consider such a class of systems is that it has shown to be suitable for input‐output modeling and control design of some turbulent flow control systems. Stability and robustness properties of the control scheme are studied by means of Volterra equations theory, which provides easily verifiable stability conditions.